PENERAPAN PERATURAN MENTERI KESEHATAN NOMOR 75 TAHUN 2014 TENTANG PUSAT KESEHATAN MASYARAKAT DI PUSKESMAS KAMPUNG BESAR KOTA KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU TAHUN 2016 - Ryan Jarisman; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Health workers have an important role to improve the quality of maximum health services to the community so that the community is able to increase awareness, willingness and ability to live healthy as referred to in the opening of the 1945 Constitution of the Republic of Indonesia. in the provision of health personnel in accordance with the needs of the community through the Regulation of the Minister of Health No. 75 of 2014, the Ministry of Health sets the standard number of health workers in each community health center and regional public hospitals so that the implementation of health services runs optimally in accordance with their workload. The formulation of the problem of this research is why the application of the health minister's regulation No. 75 of 2014 concerning community health centers has not run optimally in the the big village of the city Health Center. The purpose of the study was to determine the factors that inhibit the application of the Minister of Health Regulation No. 75 of 2014 in the Village Village Health Center in Rengat Subdistrict, Indragiri Hulu District in 2016. The method used in this study was descriptive qualitative.Based on the results of the study, it shows that the City Municipal Puskemas does not currently apply Ministerial Regulation No. 75 of 2014 concerning Public Health Centers with the unavailability of dentists, medical laboratory experts and administrative personnel. Ideally, a broad working area should be supported by the availability of health workers who can serve the community optimally. The health office and health center in this case do not establish good communication causing the shortage of health workers needed by the community not quickly handled then the socialization of the Ministerial Regulation in the City Village Health Center is not implemented optimally.Keywords: Application of Regulations, Regulation of the Minister of Health..